Acute Effect Of Active And Passive Static Stretching On Range Of Motion On Hip Joint Flexibility On Female Karate Athletes Of Muhammadiyah University Of Surakarta - Young Ari Kusworo (LPPM STIKES Guna Bangsa Yogyakarta, 2018)
Flexibility is an important component in Karate. Stretching is one way to improve the Range of Motion (ROM). Stretching static is one type of stretching that can be used. Long static stretching with low intensity is the safest form of stretching and gives significant results. The purpose of this study to determine: 1) Effect of active static stretching against on Hip joint ROM on female Karate athletes of UMS. 2) The effect of passive static stretching on hip joint ROM on female Karate athletes of UMS. 3) To know the effect of active and passive static stretching effect on Hip ROM on female Karate athletes of UMS.